2004
DOI: 10.1177/0091270004268911
|View full text |Cite
|
Sign up to set email alerts
|

Important Role of the Dihydrouracil/Uracil Ratio in Marked Interpatient Variations of Fluoropyrimidine Pharmacokinetics and Pharmacodynamics

Abstract: Dihydropyrimidine dehydrogenase (DPD) deficiency in patients causes severe toxicities in 5-fluorouracil/floxuridine (5-FU/FUDR) treatments. To determine the plasma dihydrouracil/uracil ratio (DUUR) as a potential index for setting 5-FU/FUDR doses, the authors conducted a prospective study on the relationships of the DUUR with 5-FU/FUDR pharmacokinetic and pharmacodynamic parameters. Forty gestational trophoblastic tumor (GTT) patients were treated with 30 mg/kg of 5-FU or prodrug FUDR during a 10-day cycle. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…The concentration of cytosolic protein was quantified by the Bradford method (13). A reaction mixture containing 250 Ag cytosolic protein, NADPH, buffer A, and [6][7][8][9][10][11][12][13][14] C]-5-FU was incubated for 30 minutes. Every 5 minutes, 130 AL aliquots were removed and added to an equal volume of ice-cold ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The concentration of cytosolic protein was quantified by the Bradford method (13). A reaction mixture containing 250 Ag cytosolic protein, NADPH, buffer A, and [6][7][8][9][10][11][12][13][14] C]-5-FU was incubated for 30 minutes. Every 5 minutes, 130 AL aliquots were removed and added to an equal volume of ice-cold ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, 5-FU dose optimization may be based on the plasma DUUR observed before 5-FU administration (6). Jiang et al have also showed that the pre-5-FU treatment DUUR may be a good index of DPD activity (7,8).Our laboratory recently reported the rapid noninvasive phenotypic [2-13 C]uracil breath test (UraBT) for assessment of DPD activity with 96% specificity and 100% sensitivity (9). Application of the UraBT to a large population of cancer-free subjects (n = 255) showed an observed 86% sensitivity (with 12 of 14 DPD-deficient subjects identified as DPD deficient) and…”
mentioning
confidence: 99%
See 3 more Smart Citations